Estudo de prevalência de sedentarismo nas mulheres adultas residentes na zona urbana de São Leopoldo - Masson, Carmen Rosane (Universidade do Vale do Rio do Sinos, 2004)
The objective of this study is to classify the practice of physical activities among women in São Leopoldo, RS, Brazil. A cross-sectional study of the urban population was developed in 40 census’s sectors with 1026 women aged 20 to 60 years old. Data analysis followed two paths and women were categorized as sedentary, insufficiently active or active. We observed 380 women (37.0%; CI95% 34.0 to 40.0) did not perform any physical activity in their leisure time, they were classified like sedentary. Only 37 (3.6%; CI95% 2.5 to 4.7) were classified as active. Statistically significant differences were related to social class, education, color, parity, body mass index and arterial hypertension. Based on the findings of this study, we suggested the establishment of local policies with emphasis on the implementation of public facilities and spaces for the practice of physical activities in low-income communities.
Keywords: aptidão física; atividade física; atividades de lazer; estilo de vida; exercício; and physical fitness; leisure; life style; physical activity; Ciências da Saúde